Broad distribution of spider-shaped lebensspuren along the Australian continental margin - Przeslawski, Rachel (Frontiers in Marine Science, 2022)
During feeding and burrowing, many epibenthic and infaunal animals bioturbate sediments and form a range of traces called lebensspuren (German for ‘life traces’), defined as any type of sedimentary structure produced by a living organism. During a 2020 survey along western Australia in the Gascoyne Marine Park, a distinct trace was observed several times, identical to the ‘spider trace’ observed in a 2007 survey along eastern Australia, over 4000 km away. The purpose of this brief note is to document and describe the occurrence of this unique and distinctive type of lebensspuren and to discuss ways in which similar observations may be effectively shared to increase our understanding of deep-sea biology.